2018
DOI: 10.1007/s00226-018-0991-4
|View full text |Cite
|
Sign up to set email alerts
|

Biopolyols obtained via microwave-assisted liquefaction of lignin: structure, rheological, physical and thermal properties

Abstract: The present study examined the application of polyols obtained via microwave-assisted liquefaction of lignin in the production of rigid polyurethane foam. Lignin was liquefied in crude glycerol and 1,4-butanediol at different temperatures (130-170 °C), without a catalyst and using various biomass concentrations (15 and 30 wt%). The physicochemical properties, process yield, and FTIR-based identification of the obtained polyols were investigated. Under optimal conditions, i.e., a 5-min microwave heating time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Comparing the viscosity results with values of hydroxyl number and biomass conversion for polyols obtained at 180°C, it can be concluded that at this Fig. 4 Changes in the hydroxyl number and biomass conversion after 6 h of the liquefaction process depending on the solvent used temperature, apart from the liquefaction reaction, condensation of solvents occurs, which was confirmed in other work (Gosz et al 2018). Higher liquefaction temperatures could result in generation of branched and cyclic oligoglycerols structures, which could affect chain mobility and lead to increased viscosity (Li et al 2014).…”
Section: Resultssupporting
confidence: 80%
“…Comparing the viscosity results with values of hydroxyl number and biomass conversion for polyols obtained at 180°C, it can be concluded that at this Fig. 4 Changes in the hydroxyl number and biomass conversion after 6 h of the liquefaction process depending on the solvent used temperature, apart from the liquefaction reaction, condensation of solvents occurs, which was confirmed in other work (Gosz et al 2018). Higher liquefaction temperatures could result in generation of branched and cyclic oligoglycerols structures, which could affect chain mobility and lead to increased viscosity (Li et al 2014).…”
Section: Resultssupporting
confidence: 80%
“…Similar to the varying liquefaction results for different ligneous plants, the species of microalgae was also found to be an important factor. Other raw materials that have been studied and found to influence liquefaction conversion and product properties include type of waste paper and source of lignin [27,28,30,48,49].…”
Section: Lignocellulosic Biomass Sources Formentioning
confidence: 99%
“…Various lignocellulosic biomass types such as poplar, southern pine, bamboo, bagasse, agricultural residues, and lignin have been microwave liquefied in alcohol solvents to produce PU foams. As shown in Figure 2, under different liquefaction conditions (the mass ratio of bagasse flour and biocomponent polyhydric alcohol was 1 : 2, 1 : 3, and 1 : 4 and the temperature was 125°C and 150°C), all the synthesized PU foams were of rigid type and the foam was darker in color with the addition of the liquefied bagasse [49,60,[74][75][76][77][78][79][80]. The properties of the fabricated biobased foams from microwave-liquefied products were largely dependent on the biomass type, heating methods, and liquefaction conditions.…”
Section: Integrated Utilization Of Liquefied Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“…Piszczyk et al investigated the conversion of lignin to biopolyols via microwave assisted liquefaction in crude glycerol and 1,4-butanediol at mild reaction conditions (temperature of 130-170 • C) [48]. Finally, a polyol with a hydroxyl number of 670 mg KOH/g was achieved with a yield of 93%, and liquefied biopolyol could be directly used for the production of rigid polyurethane foams.…”
Section: Hydrogen Donor Solvent Of Multi-componentmentioning
confidence: 99%